2023
DOI: 10.3390/cosmetics10040109
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Botanical Shampoo Infused with Standardised Mangosteen Peel Extract for Healthy Hair and Scalp

Abstract: In recent decades, there has been a growing demand for shampoos derived from botanical sources due to their avoidance of synthetic and highly allergenic chemicals used as bioactives and excipients. These hair care products are free from sulfates, parabens, silicones, synthetic fragrances, and artificial colours. Natural shampoos are sustainable, skin-friendly, and eco-friendly to the environment. Garcinia mangostana (Mangosteen) peel is usually discarded as agricultural waste. It consists of numerous bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although the surface of the hair washed by both shampoos was smoother than the original hair, the surface of the hair washed by VFDprocessed organic shampoo (Figure 10) showed the best smoothness, which indicated the best cleansing function. Sang et al 48 reported a positive correlation between the foaming capability and cleansing function of shampoo products; the impact of licorice shampoo on obviation of hair problems was improved with better foaming capacity.…”
Section: Rheological Properties Of Organic Shampoo Immediately After ...mentioning
confidence: 99%
“…Although the surface of the hair washed by both shampoos was smoother than the original hair, the surface of the hair washed by VFDprocessed organic shampoo (Figure 10) showed the best smoothness, which indicated the best cleansing function. Sang et al 48 reported a positive correlation between the foaming capability and cleansing function of shampoo products; the impact of licorice shampoo on obviation of hair problems was improved with better foaming capacity.…”
Section: Rheological Properties Of Organic Shampoo Immediately After ...mentioning
confidence: 99%
“…More consumers prefer to use plant-based hair shampoos, which are natural and sustainable. Recent reports show that formulated herbal shampoos can also be equivalent to commercially available ones [7]. Compared to other preparations, the formulation of shampoo preparation in the gel is preferable due to some advantages, such as the high viscosity and adhesion that prevent the gel from flowing too quickly on the skin surface, the pseudoplastic property that makes it easy to spread when applied, no marks left, the film-like thin layer when applied, the easily-washed property, and the cool sensation after use [8,9].…”
Section: Introductionmentioning
confidence: 99%